Description of a new species of Neoparaphytoseius Chant and McMurtry (Acari: Mesostigmata: Phytoseiidae) from Peru, with a redefinition of the genus - Jimenez, Sofia [UNESP]; McMurtry, James A.; De Moraes, Gilberto J. (Magnolia Press, 2014)
Neoparaphytoseius charapa n. sp. is described, based on the morphology of adult females and males collected on Inga edulis ( Mart.) ( Fabaceae) in northeastern Peru. Neoparaphytoseius Chant & McMurtry is redefined on the basis of the new species and re-examination of its type species N. sooretamus Chant & McMurtry.
Keywords: Taxonomy; Biological control; Predator; Neoparaphytoseius